Peningkatan Efektivitas Bimbingan dan Konseling Melalui Konseling Ranah Afektif - Argina Farenta; Novi Fayza Widi Putantri; Annisa Rahman; Denisa Septiani; Minarsi Minarsi (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This article discusses the importance of learning evaluation, particularly in the affective domain, which not only functions as a measurement of learning outcomes but also makes a significant contribution to Guidance and Counseling (GC) services in schools. The affective domain, which encompasses students’ attitudes, values, motivation, and character, plays a major role in shaping their social and personal behavior. This study employs a literature review method by examining articles, journals, and national conference proceedings published between 2016–2025 that are relevant to affective evaluation and its implications for GC services. The findings show that affective evaluation can provide objective data regarding the development of students’ attitudes, which is highly useful for school counselors in designing appropriate counseling programs. In addition, the development of valid and reliable assessment instruments, along with the use of digital technology, has been proven to improve the effectiveness of evaluation while also supporting more accurate diagnoses of students’ problems. Therefore, collaboration between subject teachers and school counselors is key to optimizing the use of evaluation results in supporting students’ comprehensive development.